Coconut residue as biopolymer drag reducer agent in water injection system - Salehudin, S.S. (Research India Publications, 2016)
This study describes the synthesizing of biopolymer, Carboxymethylcellulose (CMC), and study its effectiveness in drag reduction at different concentration and flow rate. The CMC was synthesized from cocos nucifera residue under the alkali-catalyzed reaction. The effectiveness of drag reduction ability was assessed by using flow loop, where the pressure drop across a length of the pipe was measured. This research concerns on the application of water injection system due to the environmental issues. The accumulation of the injected synthetic Drag Reducing Agent (DRA) in the formation causes pollution because of its chemical contents. Thus, the CMC was synthesized in this research with the objective to serve as a feasible alternative of synthetic DRAs. This study showed that for every 30 g of dried cellulose powder, 27.18 g to 28.77 g of CMC can be synthesized at the controlled condition. The effectiveness of CMC differed significantly at different concentration and different flow rate. Â© Research India Publications.